CONSTRUCTION WITH SMALL-DIAMETER ROUNDWOOD. - STERN, E. GEORGE
LARGE QUANTITIES OF SMALL-DIAMETER ROUNDWOOD ARE READILY AVAILABLE FROM COMMERCIAL FOREST THINNINGS AND OTHER HARVESTING PRACTICES. ITS USE IN CONSTRUCTION HAS BEEN LIMITED MAINLY BECAUSE OF THE LACK OF GRADING STANDARDS AND EXPERIENCE IN EFFICIENTLY.....
Sala de Colecciones abiertas
Inglés
FORE
Keywords: CONSTRUCCION EN MADERA; APROVECHAMIENTO FORESTAL; Artículos de revista